School Head Literacy Leadership Functions and the School Reading Level Of Key Stage 2: An Input to Retooling Program for Literacy Instructional Leadership - Alona M. Raton (Research Synergy Foundation, 2025)
This study aimed to determine the implication of the school heads’ literacy instructional leadership functions to the school reading level of the Key Stage 2 in the select public elementary schools in the City School Division of Cabuyao. The researcher used a quantitative descriptive method that used questionnaire survey in gathering data from 142 Key Stage 2 teachers and six public elementary school heads in Cabuyao City. The following statistical tools in the conduct of the study were used: Frequency and percentage for respondents’ profile; Weighted Mean for the literacy leadership practices; t-test for significant differences in the perception of teachers and school heads on the literacy leadership functions; and the Pearson R to determine the relationship of the school heads’ literacy instructional leadership functions and the Key Stage 2 reading level. On the findings of the study, the two sets of respondents’ perceptions of the school heads’ level of practice of the literacy leadership functions has an Overall Mean difference of 0.12 and computed t-value of .0671; as a result, the null hypothesis remained valid, but the importance of the monitoring and assessment strand was shown. On the test of a significant relationship between the school heads’ literacy leadership functions and the school reading profile, the computed r-value is .050, which implies a fragile association between the two variables, and the computed p-value is .925, which resulted in no evidence against the null hypothesis. Hence, there is no significant relationship between the literacy leadership functions and the school reading profile.